Mothers’ and teachers’ beliefs about the learning process for reading and writing in Preschool Education - Palos Toscano, María Úrsula (2017)
The learning process for reading and writing is a major achievement in any educational system, therefore it is important in the development of complex cognitive skills that enable people to cope daily life requirements. This study starts with the premise that in the development for reading and writing learning the interactions at home and school play a decisive role that is why this study aimed to analyze the beliefs that mothers and teachers formulated about preschool and how they influence the development of skills for reading and writing. Through a qualitative approach, the point of view of the participants described regarding the purpose of preschool education and how it involves them. The findings support the conclusion that the vision of the kindergarten as entertainment space and care has been overcome, however regarding for reading and writing processes there is confusion and a tendency to simply reduce them to decoding. Finally, the study highlights the importance of identifying and developing models that support these processes and co-responsibility that parents collaborate to ensure access and successful participation in initiatives that promote skills for building the reading and writing comprehension.